FORMULASI DAN UJI ORGANOLEPTIK TEH CELUP DAUN KERSEN (Muntingia calabura L.) UNTUK MEMELIHARA KADAR GULA DARAH DAN PENAMBAHAN RIMPANG JAHE (Zingiber officinale) SEBAGAI PENGHANGAT TUBUH - Tiyani, Ulis; Suharti, Suharti; Andriani, Susi (Journal of Holistic and Health Sciences (Jurnal Ilmu Holistik dan Kesehatan), 2020)
Background: DM (Diabetes Mellitus) according to the Ministry of Health (2014) is a metabolic disease caused by damage to the pancreas which causes insufficient insulin production for the body.  Objective: The aim of this study was to formulate and test organoleptic tea bags of cherry leaves (Muntingia calabura L) to maintain blood sugar levels and add ginger (Zingiber officinale) as a body warmer that is easy and practical for consumption by the public.  Method: The research method used is action research (Action Research) using research instruments in the form of organoleptic test sheets and preference tests.  Preparations are made with the composition ratio of cherry leaves of ginger root (2.5: 1, 2.5: 2, and 2.5: 3).  Results: The results showed that the drying loss of cherry leaves was 6.6% and ginger rhizome was 6%, this is in accordance with the simplicia requirements, namely water content less than 10%.  Organoleptically viewed from the formulation of bay leaf tea bag and ginger rhizome stable for 3 weeks with storage at room temperature and cold temperature with the proportion of the formula favored by the respondent, namely formula 2 with a composition of 2.5 gran kersen leaves and 2 grams of ginger rhizome is 97, 67%.  Conclusion: The conclusion of this study is that the tea bag that is preferred by the public is the second formula, namely the addition of 2 grams of ginger rhizome and a stable preparation in storage for 3 weeks at room temperature and cold temperature.